Islam and Democracy: A Study of Maudhu'i's Interpretation: Islam dan Demokrasi: Kajian Tafsir Maudhu'i - Deva Nurfazri; Dwi Nur Agustin (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2024)
This essay discusses the norms of the Koran that underlie democracy. This research originates from Muslim intellectual circles regarding the relationship between Islam and democracy. There are three points of view that emerge from this: first, the existence of a mutualistic symbiotic relationship between Islam and democracy, which states that Islam and democracy are mutually dependent and complementary; the second is an antagonistic relationship, which states that Islam and democracy, which originate from the West, are incompatible; Third, it adheres to the relationship between Islam and democracy but provides a critical note known as a critical-reactive or reciprocal-critical approach. According to this perspective, Islamic principles, namely ash-shura (deliberation), al-musawah (equality), and al-ilah (justice) are the ethical ideals that underlie democracy. There are verses in the Qur'an which form the basis for the third basic normative concept of democracy. Therefore, democracy has absolutely nothing to do with the Koran. The Qur'an specifically provides a moral foundation for building a democratic system.